Pengaruh Integrated Marketing Communication (IMC) dan Service Quality Terhadap Kepuasan Nasabah Bank Syariah Indonesia Cabang Setiabudi Kota Medan : Pengabdian - Ummaina Rahma; Onan Marakali Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the relationship between Integrated Marketing Communication (IMC) and Service Quality to Customer Satisfaction of Bank Syariah Indonesia Setiabudi Branch, Medan. This study also aims to determine the individual and combined influence of both variables on Customer Satisfaction of Bank Syariah Indonesia Setiabudi Branch, Medan, both partially and simultaneously. This study uses a quantitative research with an associative approach. Primary data was obtained through questionnaire distribution filled by 100 respondents selected using purposive sampling. Meanwhile, secondary data is obtained through references and previous research. The data were analyzed using instrument tests, classical assumption tests, multiple linear regression analysis, and regression model tests. The results show that Integrated Marketing Communication (IMC) has a positive and significant effect on Customer Satisfaction, with t-value of 7.269 > 1.660 and a significance value of 0.000 < 0.05, and a positive regression coefficient value of 0.348. Meanwhile, Service Quality also had a positive and significant effect on Customer Satisfaction, with t-value of 5.488 > 1.660 and a significance of 0.000 < 0.05, and a positive regression coefficient value of 0.389. In the simultaneous test, the IMC and Service Quality variables had a combined effect on Customer Satisfaction, with an F-value of 126.499 > 3.09 and a significance of 0.000 < 0.05, and an influence level of 71.7%, while the remaining 28.3% was influenced by other factors outside the research model.